Estimating the global investment gap in research and innovation for sustainable agriculture intensification in the Global South. - International Food Policy Research Institute (Commission on Sustainable Agriculture Intensification, 2021)
Sustainable food production needs to increase if it is to meet the rising and evolving food demands caused by growing populations, increasing incomes and urbanization. However, it faces numerous challenges. Competition for water resources is increasing – not only between people and the natural environment, but between cities and rural areas as well. Overuse of water due to wasteful irrigation management is worsening water scarcity. Climate change is bringing higher temperatures and changing precipitation patterns, as well as a higher likelihood of increased weather variability and extreme events. At the same time, agriculture is a major contributor to greenhouse gas (GHG) emissions, so sustainable agriculture intensification also needs to address climate change by reducing GHG emissions and sequestering carbon.